UV Raman studies of channel stress in transistors with embedded SiGe source and drain - Wong, Choun Pei (2012)
Channel strain engineering is important for improving the performance of metal-oxide-semiconductor (MOS) devices today. UV Raman spectroscopy is commonly used for stress measurements in microelectronics applications, but its use in channel stress studies of advanced transistors in sub-100nm nodes is relatively unexplored. This thesis presents a low-cost method for rapid characterization of channel stress of 45nm-node transistors with embedded SiGe source and drain, using UV Raman spectroscopy. Results of using a micro-meter sized laser beam to study the channel stress of repeating transistors are presented and discussed. The effects of changing the gate pitch as well as the impact of implantation and annealing on the channel stress are investigated. Simulation results are also included to provide insight into the interaction of light with the structures studied. The measurement approach presented in this thesis can be an attractive alternative to other approaches that require more time and resources to carry out.